2018
DOI: 10.1163/15685411-00003167
|View full text |Cite
|
Sign up to set email alerts
|

Steinernema borjomiense n. sp. (Rhabditida: Steinernematidae), a new entomopathogenic nematode from Georgia

Abstract: Summary A new species of entomopathogenic nematode, Steinernema borjomiense n. sp., was isolated from the body of the host insect, Oryctes nasicornis (Coleoptera: Scarabaeidae), in Georgia, in the territory of Borjomi-Kharagauli. Morphological characters indicate that the new species is closely related to species of the feltiae-group. The infective juveniles are characterised by the following morphological characters: body length of 879 (777-989) μm, distance between the head and excretory pore = 72 (62-80) μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Comparison of the ITS sequences among Steinernema species has also showed higher variability than either the D2-D3 expansion domains of the 28SrRNA gene or the partial 18S rRNA gene ( 61 ). Analysis of partial mitochondrial COI sequences among Steinernema species has revealed that fewer clades could be resolved by this method than with ITS ( 61 ), despite the plurality of informative sites available for COI sequences.…”
Section: Identification Of Epn Strains Via Dna Analysismentioning
confidence: 99%
“…Comparison of the ITS sequences among Steinernema species has also showed higher variability than either the D2-D3 expansion domains of the 28SrRNA gene or the partial 18S rRNA gene ( 61 ). Analysis of partial mitochondrial COI sequences among Steinernema species has revealed that fewer clades could be resolved by this method than with ITS ( 61 ), despite the plurality of informative sites available for COI sequences.…”
Section: Identification Of Epn Strains Via Dna Analysismentioning
confidence: 99%
“…Under the laboratory conditions, we also tested suspensions of entomopathogenic nematodes, since this group of pathogens is one of the most effectively used to regulate the number of pests, and specifically pentatomide [18]. We found that 3 days after infection with nematodes, up to (75.2 + 3.4 %) -(84.3 + 2.7) % of the N viridula imago died (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Later 85 valid species were proposed, 15 of these in the 1990s, 39 from 2000-2009 and 31 from 2010 to the beginning of 2016. From 2017 to 2018, 12 valid species were reported of which two were recently added to the list of new species, one from South Africa, S. Litchii (Steyn et al, 2017) and other from Georgia, S. borjomiense (Gorgadze et al, 2018).…”
Section: Diversity and Distribution Of Entomopathogenic Nematodes Wormentioning
confidence: 99%